The Invention of Papal History: Onofrio Panvinio between Renaissance and Catholic Reform - Stenhouse, William (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2020)
Stefan Bauer, The Invention of Papal History: Onofrio Panvinio between Renaissance and Catholic Reform, Oxford, Oxford University Press, Oxford-Warburg Studies, 2020, 288 págs., ISBN 978-0-19-880700-1 [Reseña]